2019
DOI: 10.1177/2325967119879927
|View full text |Cite
|
Sign up to set email alerts
|

Clavicle Elevation or Shoulder Girdle Depression in Acromioclavicular Joint Dislocation: A Radiological Investigation

Abstract: Background: The side-comparative coracoclavicular (CC) distance is used to describe the vertical instability component of acute acromioclavicular (AC) joint dislocations. Elevation of the clavicle or a depression of the shoulder girdle can lead to an increased CC distance. The dislocation direction has not yet been investigated and is not included in common classification systems. Hypothesis: Clavicle elevation is primarily responsible for vertical dislocation in AC joint separation. Study Design: Cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
1
9
1
Order By: Relevance
“…Regarding elevation of the clavicle, a significantly increased elevation was seen in the starting position in the lesioned condition (Figure 3B). Together with the simultaneous inferior translation of 10 mm of the scapula compared with the clavicle, the presence of a combined elevation of the clavicle and depression of the shoulder girdle in a Rockwood V lesion can be confirmed, as reported by Azar et al 2 (Figure 7). Again, Oki et al 21 also found an increased elevation in a Rockwood V injury but, in contrast to our findings, not at the start but only between 95° and 110° of coronal plane elevation.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Regarding elevation of the clavicle, a significantly increased elevation was seen in the starting position in the lesioned condition (Figure 3B). Together with the simultaneous inferior translation of 10 mm of the scapula compared with the clavicle, the presence of a combined elevation of the clavicle and depression of the shoulder girdle in a Rockwood V lesion can be confirmed, as reported by Azar et al 2 (Figure 7). Again, Oki et al 21 also found an increased elevation in a Rockwood V injury but, in contrast to our findings, not at the start but only between 95° and 110° of coronal plane elevation.…”
Section: Discussionsupporting
confidence: 65%
“…26 The 3-dimensional kinematics of the SC, ST, and AC joints were measured. A total of 6 movements were analyzed: 3 humerothoracic movements ( [1] elevation in the coronal plane, [2] elevation in the sagittal plane, [3] horizontal adduction) and 3 ST movements ([4] protraction, [5] retraction, and [6] shrug). Coronal plane elevation started with the arm at the side and was performed with the elbow extended and the thumb pointing up until complete elevation.…”
Section: Experiments Protocolmentioning
confidence: 99%
“…We should include examination of the AC joint to diagnose the dislocation correctly. For example, magnetic resonance imaging 1 and weighted radiographs with checking bilateral CC distance 2 would better discriminate between type 2 and 3 injuries. The AC ligament is said to help the horizontal stability of the AC joint; our results demonstrate that it also aids in superior stability.…”
Section: Discussionmentioning
confidence: 99%
“…The deltoid muscle normally acts as a clavicular depressor, counteracting the elevation produced by the sternocleidomastoid and trapezius muscles (5,35). When the clavicular attachments of this muscle are disrupted, the elevators are unopposed, enabling superior clavicular migration while the remaining shoulder girdle sags inferiorly, resulting in wide diastasis of the CC space (58,65).…”
Section: Rockwood Classificationmentioning
confidence: 99%